A comparison of repeated low-level red light and low-dose atropine for myopia control: A two-year retrospective study - Mingming Zhang; Yinghui Shi; Yuexin Wang; Yangguang Li; Jian Qin; Xiaobing Wang; Ying Jie (Photodiagnosis and Photodynamic Therapy)
Purpose: To compare the long-term efficacy between repeated low-level red light (RLRL) therapy and low-dose atropine (LDA) eye drops for myopia control. Methods: Treatment naïve myopic children receiving RLRL or LDA therapy were retrospectively included. The spherical equivalent (SE) and axial length (AL) were evaluated at baseline and 6-, 12-, and 24-month follow-up. The myopia progression and regression were compared between groups. Results: In total, 122 myopic children were enrolled. The SE progression and AL elongation were significantly less in the RLRL than in the LDA group at 6 months (P = 0.002, SE; P = 0.004, AL), 12 months (P < 0.001) and 24 months (P < 0.001). For patients with RLRL, the SE progression was greater during the second than the first year (P = 0.05). The proportion of patients with SE regression in the RLRL group was greater than that in the LDA group at 12 months (P = 0.003), and the AL shortening proportion was significantly greater in the RLRL group than in the LDA group at 6 months (P = 0.001), 12 months (P = 0.001), and 24 months (P = 0.049). Eight adverse events were reported in the RLRL group without irreversible structural damage. Conclusion: The present research demonstrates that RLRL treatment is more effective than 0.01 % atropine in delaying myopia progression and observes a greater percentage of patients with SE regression and AL shortening in myopic children over two years.